A newly developed strain of Enterococcus faecium isolated from fresh dairy products to be used as a probiotic in lactating Holstein cows - Azzaz, Hossam H.; Kholif, Ahmed E.; Murad, Hussein A.; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the ability of an isolated strain (EGY_NRC1) or commercial (NCIMB 11181) Enterococcus faecium as a probiotic for lactating cows. Two experiments were conducted: In Experiment 1, the effects of three levels (1, 2, and 3 g/kg diet, DM basis) of isolated and commercial E. faecium on in vitro ruminal fermentation kinetics, gas, methane (CH4) and nutrient degradability were determined. In Experiment 2, thirty multiparous Holstein cows (633 ± 25.4 kg body weight) with 7 days in milk, were randomly assigned to 3 treatments in a completely randomized design in a 60-day experiment. Cows were fed without any additives (control treatment) or supplemented with 2 g/kg feed daily of E. faecium EGY_NRC1 (contain 1.1 × 109 CFU/g) or commercial E. faecium NCIMB 11181 (contain 2 × 1012 CFU/g). Diets were prepared to meet cow's nutrient requirements according to NRC recommendations. Probiotic doses were based on the in vitro Experiment 1. Feed intake, digestibility, blood parameters and lactation performance were evaluated. In Experiment 1, the isolated E. faecium linearly and quadratically increased (P < 0.001) in vitro total gas production (TGP), the degradability of dry matter (dDM) and organic matter (dOM) while decreased (P < 0.05) methane (CH4) percent of TGP, NH3CH4 production, and pH. The commercial E. faecium increased TGP and decreased (P < 0.01) CH4 production, pH and increased the dDM and dOM, short chain fatty acids and ruminal NH3-N concentration. In Experiment 2, the isolated E. faecium increased (P < 0.01) total tract digestibility of DM, neutral and acid detergent fiber, daily milk production and feed efficiency compared to the control treatment without affecting feed intake and milk composition. Moreover, the isolated E. faecium increased (P < 0.05) the proportion of C18:1 trans-9, C18:2 cis-9-12 and C18:2 trans-10 cis-12. Both isolated and commercial E. faecium improved (P < 0.01) organic matter, crude protein and nonstructural carbohydrates digestibility, increased serum glucose (P = 0.002) and decreased serum cholesterol (P = 0.002). Additionally, both E. faecium strains decreased C23:0 (P = 0.005) in milk. In conclusion, the use of E. faecium (isolated and commercial) at 2 g/kg DM of feed improved feed efficiency and production performance, with superior effects on animal performance from isolated E. faecium compared to the commercial one.